An in-depth comparative FEA on through-thickness residual stresses in press-braked cold-formed steel section - Mutafi, Ayad; Irwan, J.M.; Yidris, Noorfaizal; Ghaleb, Atef M.; Al-Alimi, Sami; Amran, Mugahed; Qasem, Maged; Hasan, Mousa; Al-Fakih, Amin (Elsevier, 2024)
The finite element (FE) is one of the techniques implemented to predict residual stresses. The selection of the proper FE technique is essential to achieve accurate results. This study investigated the prediction of residual stress distribution in pressed-braked thin-walled cold-formed steel sections using the 3D-Shell finite element (FE) technique. Cold-forming processes produce residual stresses and affect the structural capacity of thin-walled cold-formed steel sections. Previous studies have used and recommended the 3D-Solid FE technique to predict residual stresses; however, limited studies have applied this 3D-Shell FE technique. Therefore, the results showed this study had compared the longitudinal/transverse residual stresses and the neutral axis shift obtained by the 3D-Shell FE technique with the results from the literature using the 3D-Solid FE technique. It is also revealed that there are limitations in the 3D-Shell FE technique for predicting residual stresses. © 2024 The Authors